2003
DOI: 10.1038/sj.leu.2403141
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt chloride and low oxygen tension trigger differentiation of acute myeloid leukemic cells: possible mediation of hypoxia-inducible factor-1α

Abstract: Cellular and systemic O 2 concentrations are tightly regulated to maintain delicate oxygen homeostasis. Although the roles of hypoxia in solid tumors have been widely studied, few studies were reported regarding the possible effects of hypoxia on leukemic cells. Here, we showed for the first time that low concentrations of cobalt chloride (CoCl 2 ), a hypoxia-mimicking agent, and 2-3% O 2 triggered differentiation of various subtypes of human acute myeloid leukemic (AML) cell lines, including NB4, U937 and Kas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 29 publications
9
88
0
Order By: Relevance
“…Suppression of HIF-1a expression by shRNAs remarkably blocks hypoxia-induced differentiation of myeloid cells Consistent with our previous reports (Huang et al, 2003), 50 mM of CoCl 2 and 2% O 2 , which induced HIF1a protein accumulation (Figure 3a), could trigger U937 cells to undergo granulocytic differentiation, as evidenced by morphology (Supplementary Figure S1) and CD11 expression ( Figure 3b). To validate further the role of HIF-1a protein in the hypoxia-induced differentiation, three pairs of shRNAs specifically against HIF-1a mRNA were respectively transfected into the parental U937 cells with negative control shRNA as a control.…”
Section: Hif-1a Induction Triggers Differentiation With Growth Arrestsupporting
confidence: 91%
See 1 more Smart Citation
“…Suppression of HIF-1a expression by shRNAs remarkably blocks hypoxia-induced differentiation of myeloid cells Consistent with our previous reports (Huang et al, 2003), 50 mM of CoCl 2 and 2% O 2 , which induced HIF1a protein accumulation (Figure 3a), could trigger U937 cells to undergo granulocytic differentiation, as evidenced by morphology (Supplementary Figure S1) and CD11 expression ( Figure 3b). To validate further the role of HIF-1a protein in the hypoxia-induced differentiation, three pairs of shRNAs specifically against HIF-1a mRNA were respectively transfected into the parental U937 cells with negative control shRNA as a control.…”
Section: Hif-1a Induction Triggers Differentiation With Growth Arrestsupporting
confidence: 91%
“…Our recent works found that 2% O 2 and nontoxic concentrations of CoCl 2 /DFO induce myeloid leukemic cells to undergo differentiation (Huang et al, 2003;Jiang et al, 2005). Intermittent hypoxia also significantly prolongs the survival of the transplanted acute promyelocytic leukemia (APL) mice with inhibition of infiltration and differentiation induction of leukemic cells .…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, hypoxia also decreased the expression of miR-17 and miR-20a in both AML cell lines (Supplementary Figures S3B, C S4B and C). Consistent with previous findings, 5,15 hypoxia also triggered growth arrest (Supplementary Figures S3D and S4D) and differentiation, as evidenced by the expression of CD11c, a mature myeloid cell surface marker (Supplementary Figures S3E and S4E). Moreover, when HIF-1a was knocked down in the parental U937 cell line, hypoxia-induced miR-17 and miR-20a downregulation (Supplementary Figures S5A-C) was abrogated, suggesting that HIF-1a suppresses miR-17 and miR-20a expression during hypoxia.…”
Section: Resultssupporting
confidence: 76%
“…1,3 Although a hypoxic microenvironment is regarded as a hallmark of solid tumors, and hypoxia-stabilized HIF-1a protein contributes to tumor growth, angiogenesis, and metastasis, 4 several groups, including our own, have reported that HIF-1a protein can trigger acute myeloid leukemia (AML) cells to undergo differentiation through a transcription-independent mechanism, inhibiting the progression of AML. [5][6][7][8][9] MicroRNAs (miRNAs) are a distinct class of small noncoding RNAs of around 22 nucleotides in length that posttranscriptionally repress expression of target genes through imperfect base pairing with the 3 0 untranslated region (UTR), leading to the reduced translation and degradation of the mRNA. MiRNAs have been widely associated with the development of major diseases.…”
mentioning
confidence: 99%
“…This reminded us of the fact that transcription activation of the antiapoptotic BCL-2 gene by AML1-ETO, but not Runx1 in U937 cells, requires the presence of both the runt domain and the C-terminal portion of AML1-ETO (Klampfer et al, 1996). More recently, hypoxia/HIF-1a is reported to induce differentiation of AML cells and enhances the granulocytic differentiation of normal hematopoietic cell line 32Dcl3 (Huang et al, 2003;Jiang et al, 2005;Liu et al, 2006;Nguyen-Khac et al, 2006). Recently, we also proposed that HIF-1a-induced leukemic cell differentiation is independent of its transcriptional activity (Song et al, 2007).…”
Section: Discussionmentioning
confidence: 98%